A minocycline-releasing PMMA system as a space maintainer for staged bone reconstructions—in vitro antibacterial, cytocompatibility and anti-inflammatory characterization. (6th June 2017) - Silva, Tiago; Grenho, Liliana; Barros, Joana; Silva, José Carlos; Pinto, Rosana V; Matos, Ana; Colaço, Bruno; Fernandes, Maria Helena; Bettencourt, Ana; Gomes, Pedro S
Abstract: In the present work, we study the development and biological characterization of a polymethyl methacrylate (PMMA)-based minocycline delivery system, to be used as a space maintainer within craniofacial staged regenerative interventions. The developed delivery systems were characterized regarding solid state characteristics and assayed in vitro for antibacterial and anti-inflammatory activity, and cytocompatibility with human bone cells. A drug release profile allowed for an initial burst release and a more sustained and controlled release over time, with minimum inhibitory concentrations for the assayed and relevant pathogenic bacteria (i.e., Staphylococcus aureus, slime-producer Staphylococcus epidermidis and Escherichia coli ) being easily attained in the early time points, and sustained up to 72 h. Furthermore, an improved osteoblastic cell response—with enhancement of cell adhesion and cell proliferation—and increased anti-inflammatory activity were verified in developed systems, compared to a control (non minocycline-loaded PMMA cement). The obtained results converge to support the possible efficacy of the developed PMMA-based minocycline delivery systems for the clinical management of complex craniofacial trauma. Here, biomaterials with space maintenance properties are necessary for the management of staged reconstructive approaches, thus minimizing the risk of peri-operative infections and enhancing the local tissue healing and early stages of regeneration.